Post-fire salvage logging alters a key plant-animal interaction for forest regeneration - Castro, J.; Puerta-Pinero, C.; Leverkus, A. B.; Moreno-Rueda, G.; Sanchez-Miranda, A. (ECOSPHERE, 2012)
Post-fire salvage logging is widely implemented worldwide, but there is an increasing concern about its potential impact on the ecosystem. Moreover, there is scant information about the effect of salvage logging on ecosystem processes mediated by species interactions. We manipulated a burnt pine forest to experimentally analyze the effect of burnt-wood management on the colonization of Holm oak (Quercus ilex) mediated by acorn dispersal by Eurasian jays (Garrulus glandarius). Three replicates of three treatments were established in an 18-ha plot: salvage logging (SL), non-intervention (NI), and partial cut plus lopping (PCL; felling and lopping most of the trees but leaving all the biomass in situ). We hypothesized that different burnt-wood management could alter jays' landscape perception and thus the pattern of seed dispersal and seedling recruitment. We monitored jay abundance in each treatment for three winters and three breeding periods, and jay flights of potential acorn dispersal between nearby oak trees and the treatments. We also searched for oak seedlings recruited in the experimental plot for five years following the fire. Jays were recorded significantly more times (87%) in NI, and movements to this treatment during the acorn dispersal period were also more frequent (81% of the flights). Oak seedlings were also more abundant in NI (ca. 55%) than in SL or PCL (ca. 25% each), despite a strong effect of small remnants of live pines. The results show that the burnt forest, if unsalvaged, still provides a suitable habitat for jays, while salvage logging reduces the strength of this key plant-animal interaction for oak natural regeneration. Nonintervention policies after a forest fire therefore provide the opportunity for adaptive management that helps reduce restoration costs and increase the resilience of the system.
The following values have no corresponding Zotero field: pub-location: 1990 M STREET NW, STE 700, WASHINGTON, DC 20036 USA publisher: ECOLOGICAL SOC AMER
Keywords: Garrulus glandarius; jay-oak interaction; oak colonization; Quercus ilex; resilience; salvage harvesting; seed dispersal; Sierra Nevada National Park; succession

Not only size matters: Acorn selection by the European jay (Garrulus glandarius) - Pons, Josep; Pausas, Juli G. (Acta Oecologica, 2007)
A strong selection for acorn characteristics is expected to have evolved in the mutualistic relationship between the European jay (Garrulus glandarius) and the oak (Quercus spp.). Bossema’s pioneer work suggested that jays do not select acorns randomly, but rather they preferentially select some size and species. Preference for some seeds over others may have implications on plant community dynamics by conferring advantages (or disadvantages) on the selected (avoided) seed characteristics. In this paper we test to what extent jays select acorns by species and/or by size and the relation between these two traits in Mediterranean oak species. The experiments consist of a set of ﬁeld tests in which acorns from four different coexisting Mediterranean oak species (Quercus ilex, Quercus faginea, Quercus suber, and Quercus coccifera) were placed in artiﬁcial feeders accessible to wild jays. The acorns were previously measured to control individual acorn characteristics. Using video-recording techniques, we followed jay activity and the fate of each acorn (sequence of acorn selection and method of transport). Q. ilex acorns were preferred over other acorns, and Q. coccifera acorns were avoided when other acorns were available. Preference for Q. faginea and Q. suber acorns was intermediate, that is, they were preferred over Q. coccifera acorns but not over Q. ilex acorns. Large acorns were also preferred although acorn species selection was stronger than size selection. Jays selected species and size both by visual means and by using acorn area as an indicator of size. Acorns wider than 17–19 mm were carried in the bill because of throat limitation. Our results conﬁrm Bossema’s study on temperate oaks and extend it to Mediterranean oak species, revealing implications on mixed oak forest dynamics.
Keywords: Acorn selection; Garrulus glandarius; Mediterranean oak forests; Mutualism; Quercus coccifera; Quercus faginea; Quercus ilex; Quercus suber; Regeneration